Internship in clinical data management at a clinical research organization - Farrica, Anabela de Jesus Prates (2016)
The aim of this report is to describe the training activities carried out at the Data Management Sub-Unit of Eurotrials, Scientific Consultants, as part of the 2nd year of the Master’s Program in Pharmaceutical Medicine. This internship was focused on the development of skills and on gaining experience in Clinical Data Management activities. Over the course of this internship, I had the opportunity to build upon the knowledge obtained in the Bachelor’s Degree in Biomedical Sciences and in the Master’s Program in Pharmaceutical Medicine. Concepts, requirements and practices related to Clinical Data Management were explored and strengthened throghout. Furthermore, an unique perspective on the lifecycle of clinical research projects was obtained – that of a CRO. Besides the acquisition of theoretical knowledge, this training period was paramount for the development of a number of social and personal skills that contributed for my profissional growth within the host institution. This document begins by a description of the theoretical principles that set the ground for the Clinical Data Manager’s work. Then, the generic and specific training elements of the curricular training are detailed. After presenting my training activities, I discuss the various challenges I had to overcome during these 9 months. Finally, some personal remarks and conclusions are presented.